PREDICTIVE FACTORS OF BURNOUT AMONG ADAPTED PHYSICAL EDUCATION TEACHERS: A STUDY OF SOCIAL SUPPORT, WORK STRESS, AND PROFESSIONAL COMPETENCE - Jiang , Weiwei; Nazarudin, Mohamad Nizam; Mazalan, Nur Shakila (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Teacher burnout, particularly among adapted physical education (APE) teachers in special education, has a significant impact on educator well-being and instructional quality. This study examines the relationship between work stress, social support, professional competence and burnout in this group. The study aimed to (1) explore the relationships among work stress, social support, professional competence, and burnout and (2) assess the combined predictive effects of these factors on burnout using a regression model. Data were collected from 200 adapted PE teachers in special schools in Fujian Province, China, using a cross-sectional survey design. Standardised tools measured social support, work stress, professional competence, and burnout. Descriptive statistics, Pearson correlation, and hierarchical regression analyses were employed. The average scores for all variables were around 50, with standard deviations of 10.025 for social support and professional competence, and 15.037 for work stress. Correlation analysis revealed significant negative relationships between social support and burnout (r = -0.627, p < 0.001) and between professional competence and burnout (r = -0.617, p < 0.001). Conversely, work stress showed a strong positive correlation with burnout (r = 0.802, p < 0.001). The regression model indicated that work stress, social support, and professional competence together explained 81.2% of the variance in burnout (R² = 0.812). Work stress was the strongest predictor (β = 0.490, p < 0.001), followed by professional competence (β = -0.378, p < 0.001) and social support (β = -0.041, p < 0.001). These findings confirm that work stress is a primary predictor of burnout, while social support and professional competence serve as protective factors. Addressing work stress, enhancing professional skills, and strengthening social support are essential for reducing burnout. Future research should consider longitudinal studies and explore additional factors, such as work-life balance, to gain a more comprehensive understanding of burnout dynamics. Cross-cultural research could also offer insights into targeted support strategies for adapted PE teachers in diverse special education environments.